SPECTRAL OBSERVATIONS OF AB AUR - Ismailov, N. Z.; Khalilov, O. V. (Одеські астрономічні публікації, 2010)
Results of spectral observations of the Herbig Ae/Be type star AB Aur carried out for 2008 - 2009 in SHAO were presented. The absorption component of the Hα line has a negative variable dis placement on different dates, reaching -300 km/s. To this absorption component superimposed an emission peak, which is rather unstable and can disappear com pletely on time scales 3-4 day. We also studied profiles of the Hβ line and found behavior completely similar to that of Hα. The line HeI λ5876AA has a composite structure with dominant one red and blue component. Profiles of presented lines and its spectral parameters shows variability from night to night. Moreover we have also presented results of researches UV spectrograms of the star on the IUE archive data base. On this data we have measured intensities of 15 absorption lines. Our measurements allow us to catty out a monitoring of spectral parameters of the lines for 3, 6 days, and for 14 years. It was showed that since quick time variability from day-to day can be referred only for some group of lines, for 14 years observations in practice intensities of all spectral lines is showed variability with deviation larger 3 σ level. We have discovered variability with period 6 day both for 6 day and more long time data. It was showed that some lines of different elements shows different character of variability. In some case variations of lines are in similar phase, in anti-phase and free forms with each other. We supposed that the basic variability in atmosphere Aur occurs in the bottom layers of an environment, in nearby areas to the surface of the star where matter accretion velocity reaches up to 300 km/s.